Effect of recreational beach tennis on ambulatory blood pressure and physical fitness in hypertensive individuals (BAH study): rationale and study protocol - Rodrigo Ferrari; Leandro de Oliveira Carpes; Lucas Betti Domingues; Alexandre Jacobsen; Paula Frank; Nathalia Jung; Joarez Santini; Sandra C. Fuchs; The BAH Study Group (BMC, 2021)
Abstract Background Different physical activities are widely recommended as non-pharmacological therapies to reduce blood pressure. However, the effectiveness of exercise programs is associated with its continuity and regularity, and the long-term adherence to traditional exercise interventions is often low. Recreational sports emerge as an alternative, being more captivating and able to retain individuals for longer periods. Besides, sport interventions have demonstrated improvements in physical fitness components that are associated with a lower incidence of hypertension. However, no studies have investigated the effects of recreational sports on 24 h ambulatory blood pressure. The aim of the present study is to evaluate the effect of beach tennis training on ambulatory blood pressure and physical fitness in individuals with hypertension. Methods This study will be a randomized, single-blinded, two-arm, parallel, and superiority trial. Forty-two participants aged 35-65 years with previous diagnosis of hypertension will be randomized to 12 weeks of beach tennis training group (two sessions per week lasting 45-60 min) or a non-exercising control group. Ambulatory (primary outcome) and office blood pressures, cardiorespiratory fitness, muscle strength/power and quality of life will be assessed at baseline and after the intervention period. Discussion Our conceptual hypothesis is that beach tennis training will reduce ambulatory blood pressure and improve fitness parameters in middle-aged individuals with hypertension. The results of this trial are expected to provide evidences of efficacy of recreational beach tennis practice on blood pressure management and to support sport recommendations for clinical scenario in higher risk populations. Trial registration ClinicalTrials.gov, NCT03909321 . Registered on April 10, 2019.